Outcome predictors in rheumatoid arthritis - C. Montecucco (PAGEPress Publications, 2011)
Predicting which patients will develop severe rheumatoid arthritis is essential for selection of the most appropriate treatment regimen in early arthritis. The key outcomes in rheumatoid arthritis are persistence of the disease, joint damage (evaluated by X-ray progression), functional dysability, and mortality rate. Rheumatoid factor positivity and number of swollen joints appear to be related to all of these outcomes, while radiologic scores are mostly related to joint damage and health assessment questionnaire (HAQ) to functional dysability. Other relevant prognostic parameters are erythrocyte sedimentation rate or serum C-reactive protein levels, and antibodies to citrullinated peptides.